2021
DOI: 10.14207/ejsd.2021.v10n2p171
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring the Economic Security of Ukraine in the Aspect of the Association Agreement Between the EU

Abstract: The study characterizes economic security as a set of conditions that are necessary to ensure the normal economic development of the country and restore the gap in development in comparison with European countries during Ukraine's integration into the EU. It is shown that ensuring economic security is an important function of the state. The problem of economic security arises not only from the definition of the internal policy of the state, but also determines the issues of foreign strategy. The necessity of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The per capita retail sales of consumer goods are used to characterize the potential of the regional internal market. Foreign trade, as an external demand, is generally measured as investment [ 33 ], the proportion of FDI in GDP, export structure [ 29 ], foreign trade dependence [ 64 ], cross-border investment [ 24 ], etc. Due to data scarcity, the distance from border ports, instead of the indicators above, is used to measure the potential of foreign trade.…”
Section: Research Area Indicator Selection and Research Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The per capita retail sales of consumer goods are used to characterize the potential of the regional internal market. Foreign trade, as an external demand, is generally measured as investment [ 33 ], the proportion of FDI in GDP, export structure [ 29 ], foreign trade dependence [ 64 ], cross-border investment [ 24 ], etc. Due to data scarcity, the distance from border ports, instead of the indicators above, is used to measure the potential of foreign trade.…”
Section: Research Area Indicator Selection and Research Methodsmentioning
confidence: 99%
“…Secondly, the factors that affect economic security come from both inside and outside a region. The internal factors are represented by indicators including GDP growth rate [ 23 , 29 ], inflation rate [ 29 , 30 ], family saving and asset accumulation [ 32 ], employment or unemployment rate [ 2 , 30 , 31 ], industrial structure [ 29 , 33 ], government procurement of public services [ 22 ], investment in fixed assets [ 23 ], residents’ income [ 2 , 30 ], etc. The external factors mainly reflect the dependence of a country/region on the global economy or its competitiveness in the global economic system, which involves foreign investment and import and export trade, and some specific indicators, including the proportion of FDI (Foreign Direct Investment) in GDP [ 31 , 33 ], import index [ 23 , 31 ], export index [ 29 , 33 ], cross-border investment [ 24 ], foreign trade [ 30 ], foreign debts and liabilities [ 23 ], as well as comprehensive indicators reflecting the level of globalization, such as globalization index, global competitiveness (e.g., the effective integration of countries in the global value chain and their competitive advantages in key economic fields [ 2 ]), and global cooperation (e.g., the framework of regional economic cooperation and integration dealing with traditional and non-traditional issues [ 24 ]).…”
Section: Literature Review and Analytical Framework Of Resmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that now it is necessary to define the economic security of the state as a certain community of factors that ensure adequate development of the social and economic spheres and reduce the backlog of Ukraine and the eurozone countries. The determinants are presented that determine the main directions for analyzing the current state and directions for the development of the national system of socio-economic security (Mohilevskyi, L. et al 2021). The authors have developed the structure of the model of strategic planning of national economic security, which includes several levels, such as main goal, areas of national economic security, threats, concept, strategy, program, plan, activities.…”
Section: A Literature Reviewmentioning
confidence: 99%